PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATA PELAJARAN PEMELIHARAAN KELISTRIKAN KENDARAAN RINGAN DI SMKN 1 TALIWANG - Ipan Apriliswan; Ardi Widyatmoko; Subagyo (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this research is to produce learning videos and to determine the feasibility of learning videos to be applied to light vehicle electrical maintenance eyes at SMKN Taliwang. This development research uses Dick and Carry's method, which includes 5 development steps, namely Analysis, Design, Development, Implementation, Evaluation. This learning video was validated by six material experts and five media experts and then tested on 29 students of class XI TKR at SMKN 1 Taliwang using a questionnaire. The results of tie validation by material experts have an average of 4.1 with a percentage of 56% which is categorized in the appropriate criteria. Likewise, the results of the feasibility test from media experts have a value of 4.06 with a percentage of 62% which is categorized as Eligible. Then the results of the student trial get an average value of 4.134 with a percentage of 61% which is categorized in the Eligible criteria. Based on these results, it can be concluded that the learning video media on the subject of light vehicle electrical maintenance is feasible to be used in the learning process.